PEMANFAATAN KOMIK SEBAGAI MEDIA PEMBELAJARAN SEJARAH DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Pramudya Gunawan; Sujarwo (KRONIK : Journal of History Education and Historiography, 2022)
One of the subjects that is a challenge in implementing education in the 21st century is the learning process on historical subjects. The history learning method in the classroom tends to be monotonous by using the lecture method, making students easily bored and not understanding the material well. On the other, there are illustrated, easy-to-carry, and read comic media that can contain text, images, and scenes. It can be an alternative media for history learning because it stimulates students to be creative, imaginative, and innovative, as well as encourages them to be independent. This research aims to analyze the benefits of using comics as a medium to learn history to increase students' motivation and learning outcomes. This research uses a literature review method with descriptive analysis techniques. Researchers collect data from previous relevant studies in the last ten years. The results of researches that have been carried out illustrate that using comics media in history learning can significantly increase student motivation and learning outcomes.